The influence of the mechanical fatigue on the energy loss of ferromagnetic steel by magnetic method - Thinh, Van Huu; Hung, Nguyen Xuan (Vietnam Journal of Mechanics, 2005)
In this paper we present some experimental results of the influence of the fatigue on the energy loss due to hysteresis of the rotating sample made from ferromagnetic steel in the fatigue testing. By measuring and calculating the energy loss per cycle due to hysteresis, we discover the energy loss increase depending on number of fatigue cycles. The results are used for evaluating the fatigue state, the working life, and technical diagnosing for rotating samples.